2008
DOI: 10.1002/eco.16
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic and geomorphic effects on mayfly drift in high‐gradient streams at moderate discharges

Abstract: We investigated relationships between geomorphic and hydraulic factors and invertebrate drift in high-gradient streams. We measured drift density of a highly mobile mayfly (Baetis bicaudatus) into and out of 12 stream reaches in western Colorado, as well as benthic density and abiotic variables within those reaches, during a time of moderate discharge. Multiple regression analysis indicated that drift propensity (drift density/benthic density), a measure of drift standardized by the benthic density of the sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 60 publications
2
23
1
2
Order By: Relevance
“…However, Spearman correlation coefficients between the measured PM variables and flow/discharge did not corroborate this hypothesis. This observation diverges from many previous findings on particle transport that showed a strong positive relationship among hydrological predictors (i.e., discharge, flow velocity, shear stress) and transported PM (Maciolek 1966;Naiman & Sedell 1979;Wilcox et al 2008). Besides water column/near-bed hydrological conditions, particle transport in streams is greatly affected by initial benthic material distribution, substratum and channel (geo)morphology, complexity of in-stream retention structures, and biological activity (Cushing et al 1993;Cordova et al 2008;Small et al 2008).…”
Section: Patterns Of Particulate Matter Transportcontrasting
confidence: 92%
“…However, Spearman correlation coefficients between the measured PM variables and flow/discharge did not corroborate this hypothesis. This observation diverges from many previous findings on particle transport that showed a strong positive relationship among hydrological predictors (i.e., discharge, flow velocity, shear stress) and transported PM (Maciolek 1966;Naiman & Sedell 1979;Wilcox et al 2008). Besides water column/near-bed hydrological conditions, particle transport in streams is greatly affected by initial benthic material distribution, substratum and channel (geo)morphology, complexity of in-stream retention structures, and biological activity (Cushing et al 1993;Cordova et al 2008;Small et al 2008).…”
Section: Patterns Of Particulate Matter Transportcontrasting
confidence: 92%
“…Benthic invertebrates may also initiate emigration at higher rates in response to unfavorable local environmental conditions. Increased emigration may occur in areas of adverse hydrology (Fonseca and Hart, 1996;Wilcox et al, 2008;Winterbottom et al, 1997) or high predation pressure (Englund, 2005;Englund et al, 2001) that occurs in lower velocity areas (Hill and Grossman, 1993;Hughes, 1992;Malmqvist and Sackmann, 1996). The latter is especially important in the context of our simple prediction that macroinvertebrate density should be inversely proportional to flow velocity.…”
Section: Discussionmentioning
confidence: 98%
“…Predatory stoneflies are present in all streams in variable densities, which are unrelated to presence of fish . Detailed analyses of variation in chemical and physical (hydrological and geomorphological) features among streams showed that there were no significant multivariate differences between fish and fishless streams used in this study , Wilcox et al 2008. However, fishless streams tended to be smaller, and have less large protruding rocks, than fish streams (Wilcox et al 2008).…”
Section: Study Sitesmentioning
confidence: 64%